Literature and the Bible: a reader - Carruthers, Jo (Routledge literature readers, 2014)
The relationship between literature and the Bible. Introducing the study of literature and the Bible -- Ways of reading -- Reception history -- Literary reading -- Translation -- Multivocality -- Metaphor & allegory -- Theological interpretation. Parables -- Genesis -- Salvation, transformation and apocalypse